Comprehensive understanding of multiple resonance thermally activated delayed fluorescence through quantum chemistry calculations - Katsuyuki Shizu (Communications Chemistry, 2022)
Molecules that exhibit multiple resonance thermally activated delayed fluorescence (MR-TADF) are highly efficient electroluminescent materials, but their emission mechanism is still not fully understood. Here, the emission mechanism of a representative MR-TADF molecule is studied through quantum chemistry calculations, with two consecutive decay processes unveiled.